Aflatoxin B1 exposure and its association with nutritional status of children receiving cereal-based supplementary foods at health centers in Rwanda - Matabishi, Mpenda A.; Mutua, Florence; Lindahl, Johanna F.; Hahirwa, I.; Umugwaneza, M.; Musafili, A.; Munyanshongore, C. (African Scholarly Science Communications Trust, 2025)
In sub-Saharan Africa, as well as in various global tropical regions, cereal-based porridge serves as the primary dietary energy source, particularly for malnourished children who rely on these cereal-based porridge as supplementary nutritional provisions. Few studies on aflatoxin contamination in foods and feeds have been done in Rwanda; also, data on aflatoxin exposure estimate in children receiving cereal-based foods at the country's Health Center (HC) facilities are scanty. The present study aimed to investigate the association between aflatoxin B1 exposure and the nutritional status of children in Rwanda using an analytical retrospective study design. Children (n=216) aged 6–59 months were recruited from HCs in districts known to have high prevalence of chronic malnutrition. A case definition was established, wherein children with a recent diagnosis of malnutrition were included as cases. Two controls per case were considered. Urine samples were analyzed for AFM1 using enzyme-linked immunosorbent assay (ELISA). The association between AFM1 and the nutritional status of children was assessed using a multivariable logistic regression analysis in STATA 15. The results show that significantly more individuals in the case group (79.41%) had detectable AFM1 in urine compared to the number in the control group (59.57%) (p=0.002). The arithmetic means of AFM1 were approximately 1.24 ng/ml (±1.50) and 1.03 ng/ml (±3.11) for case and control groups, respectively (p=0.003). Occurrence of AFM1 in urine was significantly associated with the child's location (p=0.032). The only demographic variable associated with logarithmic AFM1 values was socioeconomic status, with category 3 (medium) exposure levels significantly higher than category 2 (poor) (p=0.031). In predicting malnutrition, children from category 1 (very poor) had significantly lower odds compared to those in category 2 (poor), while increasing AFM1 levels in urine significantly increased the odds of malnutrition. Therefore, we recommend the implementation of routine surveillance of aflatoxin levels in locally produced complementary foods, stricter enforcement of food safety regulations, and targeted public health interventions—such as educating caregivers on safe food storage and preparation practices—to reduce aflatoxin exposure among young children in high-risk areas of Rwanda.